PEMANFAATAN SMARTPHONE UNTUK DIGITAL MARKETING BAGI PKK KELURAHAN CIPINANG BESAR SELATAN - Wulandari, Arviana; Retnoningsih, Endang; Rofiah, Syahbaniar; Setiyadi, Didik; ., Jaenudin; Kurniawan, Luluh Abdilah (LPPM Univ. Ibn Khaldun Bogor, 2022)
Pemberdayaan dan Kesejahteraan Keluarga (PKK) is a forum for the public to obtain information and develop knowledge and skills in any case. Empowerment will be right on target by obtaining information that can be accessed quickly with a Smartphone as a means of gaining knowledge. With reference to the Pokja II and III work programs, namely improving education and skills in the family through training, utilizing appropriate technology and developing the creativity of Small and Micro Enterprises (UKM). The Smartphone utilization training carried out was the introduction of digital marketing using a Smartphone, the introduction of the Canva application to support the display design of digital marketing products, and the introduction of the use of social media and e-commerce for digital marketing for PKK mothers in the Cipinang Besar Selatan Sub-District. improve skills in digital marketing as a provision to open UKM.